Processed beetroot (Beta vulgaris L.) as a natural antioxidant in mayonnaise: Effects on physical stability, texture and sensory attributes - Vassilios Raikos; Angela McDonagh; Viren Ranawana; Garry Duthie (Food Science and Human Wellness)
The oxidative and physical stability of the reformulated mayonnaise with processed beetroot was investigated and compared with a control (mayonnaise without beetroot) and a commercially available product. Processing of beetroot had an impact on the structural integrity of the antioxidants present. Microwaving (960 W for 7 min) was advantageous for preserving the betalain and polyphenol content of beetroot compared to roasting (180 °C for 90 min) and boiling (100 °C for 30 min). The oxidative stability of mayonnaise samples was determined by Rancimat and the thiobarbituric (TBA) assay. The addition of microwaved beetroot significantly enhanced the oxidative stability of mayonnaise at the end of a storage period of 4 weeks (4 °C). Although no significant differences (P > 0.05) were detected between the mayonnaise samples containing beetroot and the commercial control, the latter was less susceptible to oxidation during storage. The turbiscan stability index (TSI) revealed that the commercial mayonnaise was less prone to destabilization phenomena. All the textural parameters increased with the incorporation of beetroot. The sensory evaluation revealed that, with the exception of graininess and uniformity, most of the sensory attributes are preserved if not improved with the addition of beetroot.